1993
DOI: 10.1590/s0034-89101993000500005
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes de trânsito em área metropolitana da região sul do Brasil: caracterização da vítima e das lesões

Abstract: . et al. Acidentes de trânsito em área metropolitana da região sul do Brasil -Caracterização da vítima e das lesões. Rev. Saúde Pública, 27: 350-6,1993. Por meio de estudo retrospectivo, descreve-se a casuística referente aos atendimentos prestados a acidentados de trânsito, em 1988, em hospital de Pronto Socorro de Porto Alegre, RS -Brasil. Os dados utilizados foram fornecidos pelo Setor de Documentação e Estatística do hospital estudado (n=6.099). Os resultados encontrados, similares àqueles descritos na lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
26

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 8 publications
(3 reference statements)
0
7
0
26
Order By: Relevance
“…The analysis regarding the location of injuries in 6099 victims of this event in the South of Brazil identified that the most affected body regions were the lower and upper limbs (69.7%), the head (49.6%), and the thorax (19.9%) (12) .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis regarding the location of injuries in 6099 victims of this event in the South of Brazil identified that the most affected body regions were the lower and upper limbs (69.7%), the head (49.6%), and the thorax (19.9%) (12) .…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by Chart 1, more than half of patients are within 12 -32 years old. This age group formed by teenagers and young adults is just the group mostly affected by accidents, either car, recreative or sports-related accidents (4,8,11) . Concerning the low income of patients receiving healthcare in trauma emergency rooms, it is worthy to highlight that the service where this study was conducted, due to its public nature, draws healthcare to less privileged patients, who do not have access to private hospitals or health insurances, which demonstrates the social importance of such unit.…”
Section: Discussionmentioning
confidence: 99%
“…6,13 Data on the accidents collected by the SIAT-FOR system were complemented according to the two types of relationship, involving two different stages. In the first, deterministic, stage the SIAT-FOR database, provided by the AMC, regarding vehicles which had been involved in traffi c accidents, was linked to the DETRAN-CE database using vehicle license plates to obtain information on the year and type of vehicle.…”
Section: Data From Thementioning
confidence: 99%
“…The factors that were independently associated with death by traffi c accident in the fi nal model were bicycles (OR = 21.2, 95%CI 16.1;27.8), running over pedestrians OR = 5.9 (95%CI 3.7;9.2), collision with a fi xed obstacle (OR = 5.7, 95%CI 3.1;10.5) and accidents involving motorcyclists (OR = 3.5, 95%CI 2.6;4.6). The main contributing factors were a single person being involved (OR = 6.6, 95%CI 4.1;10.73), presence of unskilled drivers (OR = 4.1, 95%CI 2.9;5.5) a single vehicle (OR = 3.9, 95%CI 2,3;6,4), male (OR = 2.5, 95%CI 1.9;3.3), traffi c on roads under federal jurisdiction (OR = 2.4, 95%CI 1.8;3.7), early morning hours (OR = 2.4, 95%CI 1.8;3.0), and Sundays (OR = 1.7, 95%CI 1.3;2.2), adjusted according to the log-binomial model. …”
mentioning
confidence: 99%